Demoulding cloth
By designing a laminated structure and a spacer layer for uniformly distributing inorganic fillers in the mold release fabric, the problem of the existing mold release fabric sticking to the mold under high temperature conditions is solved, and the convenient transfer and repeated use of the mold release fabric is achieved. Avoid glue leakage and improve mold cleaning and product quality.
Patent Information
- Application Number
- CN202420277395.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-05
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2034-02-05
AI Technical Summary
The existing mold release cloth is easily stuck to the mold under high temperature conditions and cannot be transferred and used. It may cause glue leakage, affecting the cleaning of the mold and the quality of the parts.
A mold release cloth is designed, and its structure includes a first polytetrafluoroethylene layer, a first polytetrafluoroethylene spacer layer, a glass fiber cloth, a second polytetrafluoroethylene spacer layer and a second polytetrafluoroethylene Inorganic filler is distributed in the layers and spacers. This structural design makes the mold release cloth easy to transfer and reuse, and avoids glue leakage.
It realizes convenient transfer and repeated use of mold release fabrics, avoids adhesive and glue leakage, and simplifies the mold cleaning and the production process of parts.
Smart Images

Figure CN222495743U_ABST
Abstract
Description
Technical Field
[0001] The utility model belongs to the technical field of demoulding cloths, and in particular relates to a demoulding cloth. Background Art
[0002] In the autoclave molding process, mold release cloth is often used for demoulding. Conventional mold release cloth is made of nylon or polyester. It is difficult to separate this kind of mold release cloth from the workpiece and requires a lot of effort to peel off. In addition, high-temperature mold release cloth is usually glued and directly adheres to the mold and cannot be transferred. The mold release cloth without glue will have a slight degree of glue seepage, causing the resin to penetrate into the mold surface, affecting demoulding, and requiring further cleaning of the mold, increasing the cost of part production.
[0003] CN202246525U discloses a polytetrafluoroethylene glass fiber cloth demoulding cloth, which comprises a base cloth, on the surface of which silica gel is coated; the base cloth is an alkali-free plain glass cloth, and a polytetrafluoroethylene layer is coated on the alkali-free plain glass cloth.
[0004] CN103741476A discloses a self-adhesive and easily removable polytetrafluoroethylene demoulding cloth for autoclave molding composite materials, comprising an alkali-free glass fiber cloth, a polytetrafluoroethylene layer coated on the periphery of the alkali-free glass fiber cloth, and a silicone layer sprayed on one side of the alkali-free glass fiber cloth coated with the polytetrafluoroethylene layer.
[0005] The above-disclosed release cloths are all provided with a silicone layer on a polytetrafluoroethylene layer, so as to achieve the effect of sticking on one side and not sticking on the other side. In actual application, the silicone layer sticks to the mold, so that the release cloth cannot be transferred to different molds and can only be reused on the same mold. Therefore, it is urgent to design a release cloth that can be transferred and reused without leaking glue. Utility Model Content
[0006] In view of the problems existing in the prior art, the purpose of the utility model is to provide a demoulding cloth, which, through its structural design, is easy to transfer and can be reused. It does not contain glue and only needs to be fixed with tape during laying. It is easy to demould and there will be no glue seepage.
[0007] To achieve this purpose, the utility model adopts the following technical solutions:
[0008] The utility model provides a demoulding cloth, which comprises a first polytetrafluoroethylene layer, a first polytetrafluoroethylene spacer layer, a glass fiber cloth, a second polytetrafluoroethylene spacer layer and a second polytetrafluoroethylene layer which are stacked in sequence; inorganic fillers are evenly distributed in the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer.
[0009] The schematic diagram of the cross-sectional structure of the demoulding cloth provided by the utility model is as followsFigure 1 As shown, it includes a first polytetrafluoroethylene layer 1, a first polytetrafluoroethylene spacer layer 2, a glass fiber cloth 3, a second polytetrafluoroethylene spacer layer 4, and a second polytetrafluoroethylene layer 5. Through the design of the structure, the demoulding cloth is easy to transfer and can be reused. In addition, BMI resin prepreg is used and the autoclave curing process is used. After demoulding, the resin in the prepreg will not penetrate into the surface of the mold.
[0010] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0011] Preferably, the thickness of the release cloth is 0.07-1.5 mm, for example, it can be 0.07 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm or 1.5 mm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the utility model no longer exhaustively lists the specific point values included in the range.
[0012] Preferably, the surface density of the release cloth is 120-700 g / m 2 , for example, it can be 120g / m 2 , 150g / m 2 , 200g / m 2 , 250g / m 2 , 300g / m 2 , 350g / m 2 , 400g / m 2 , 500g / m 2 , 600g / m 2 or 700g / m 2 , as well as specific point values between the above point values. Due to space limitations and for the sake of brevity, the utility model no longer exhaustively lists the specific point values included in the said range.
[0013] Preferably, the thickness of the first polytetrafluoroethylene layer and the second polytetrafluoroethylene layer are each independently 0.008-0.2 mm, for example, 0.008 mm, 0.01 mm, 0.02 mm, 0.04 mm, 0.06 mm, 0.08 mm, 0.1 mm, 0.12 mm, 0.14 mm, 0.16 mm, 0.18 mm or 0.2 mm and specific values between the above point values. Due to space limitations and for the sake of simplicity, the utility model no longer exhaustively lists the specific point values included in the said range.
[0014] Preferably, the total surface density of the first polytetrafluoroethylene layer and the second polytetrafluoroethylene layer in the release cloth is 40-200 g / m 2 , for example, it can be 40g / m 2 , 60g / m 2 , 80g / m 2 , 100g / m 2 , 120g / m 2 , 140g / m 2 , 160g / m 2 , 180g / m 2 or 200g / m 2 , as well as specific point values between the above point values. Due to space limitations and for the sake of brevity, the utility model no longer exhaustively lists the specific point values included in the said range.
[0015] Preferably, the thickness of the glass fiber cloth is 30-800 μm, for example, it can be 30 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm or 800 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the utility model no longer exhaustively lists the specific point values included in the range.
[0016] Preferably, the surface density of the glass fiber cloth is 40-200 g / m 2 , for example, it can be 40g / m 2 , 50g / m 2 , 60g / m 2 , 70g / m 2 , 80g / m 2 , 90g / m 2 , 100g / m 2 , 110g / m 2 , 120g / m 2 , 130g / m 2 , 140g / m 2 , 150g / m 2 , 160g / m 2 , 170g / m 2 , 180g / m 2 , 190g / m 2 or 200g / m 2 , as well as specific point values between the above point values. Due to space limitations and for the sake of brevity, the utility model no longer exhaustively lists the specific point values included in the said range.
[0017] Preferably, the thickness of the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer are each independently 0.008-0.3 mm, for example, 0.008 mm, 0.01 mm, 0.02 mm, 0.04 mm, 0.06 mm, 0.08 mm, 0.1 mm, 0.12 mm, 0.14 mm, 0.16 mm, 0.18 mm, 0.2 mm, 0.22 mm, 0.24 mm, 0.26 mm, 0.28 mm or 0.3 mm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the utility model no longer exhaustively lists the specific point values included in the said range.
[0018] Preferably, the total surface density of the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer in the release cloth is 40-300 g / m 2 , for example, it can be 40g / m 2 , 50g / m 2 , 60g / m 2 , 70g / m 2 , 80g / m 2 , 90g / m 2 , 100g / m 2 , 110g / m 2 , 120g / m 2 , 130g / m 2 , 140g / m 2 , 150g / m 2 , 160g / m 2 , 170g / m 2 , 180g / m 2 , 190g / m 2 , 200g / m 2 , 250g / m 2 or 300g / m 2 , as well as specific point values between the above point values. Due to space limitations and for the sake of brevity, the utility model no longer exhaustively lists the specific point values included in the said range.
[0019] Preferably, the inorganic filler includes any one of nano silicon dioxide, 3-aminopropyltriethoxysilane, nano magnesium titanate or isopropyl triisostearoyl titanate, or a combination of at least two thereof.
[0020] Preferably, the mass percentage of the inorganic filler in the first polytetrafluoroethylene spacer layer is 10-25%, for example, it can be 10%, 15%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5% or 25%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the utility model no longer exhaustively lists the specific point values included in the said range.
[0021] Preferably, the mass percentage of the inorganic filler in the second polytetrafluoroethylene spacer layer is 10-25%, for example, it can be 10%, 15%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5% or 25%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the utility model no longer exhaustively lists the specific point values included in the said range.
[0022] Preferably, under the condition of 100Pa, 20cm 2 The air permeability of the release cloth is not greater than 0.02 mm / s, for example, it can be 0.001 mm / s, 0.005 mm / s, 0.01 mm / s, 0.015 mm / s or 0.02 mm / s.
[0023] Exemplarily, the release cloth provided by the present invention is prepared by the following method, which comprises the following steps:
[0024] (1) dipping the glass fiber cloth in a first polytetrafluoroethylene emulsion containing an inorganic filler, and then sequentially performing a first coating, a first drying, a first heat treatment, and a first sintering; dipping the glass fiber cloth in a second polytetrafluoroethylene emulsion containing an inorganic filler, and then sequentially performing a second coating, a second drying, a second heat treatment, and a second sintering, to form a first polytetrafluoroethylene spacer layer and a second polytetrafluoroethylene spacer layer on both sides of the glass fiber cloth;
[0025] (2) The glass fiber cloth having the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer formed on both sides is subjected to a third immersion in a first polytetrafluoroethylene emulsion, and then subjected to a third coating, a third drying, a third heat treatment and a third sintering in sequence, and then subjected to a fourth coating, a fourth drying, a fourth heat treatment and a fourth sintering in sequence, to form a first polytetrafluoroethylene layer on the first polytetrafluoroethylene spacer layer, and a second polytetrafluoroethylene layer on the second polytetrafluoroethylene spacer layer, and finally rolled to obtain the release cloth.
[0026] Preferably, the glass fiber cloth is desized before the first impregnation.
[0027] Preferably, in the first polytetrafluoroethylene emulsion containing inorganic filler, the mass percentage of polytetrafluoroethylene is 30-40%, for example, it can be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39% or 40%.
[0028] Preferably, the first impregnation time is 3-15 s, for example, 3 s, 5 s, 6 s, 7 s, 8 s, 9 s, 10 s, 12 s or 15 s.
[0029] Preferably, the first drying temperature is 90-100°C, for example, it can be 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C or 100°C.
[0030] Preferably, the first drying time is 1-4 min, for example, it can be 1 min, 1.2 min, 1.5 min, 1.8 mins, 2 mins, 2.5 min, 3 min, 3.5 min or 4 min.
[0031] Preferably, the temperature of the first heat treatment is 280-300°C, for example, it may be 280°C, 282°C, 284°C, 286°C, 288°C, 290°C, 292°C, 294°C, 296°C, 298°C or 300°C.
[0032] Preferably, the first heat treatment time is 1-4 min, for example, it can be 1 min, 1.2 min, 1.5 min, 1.8 mins, 2 mins, 2.5 min, 3 min, 3.5 min or 4 min.
[0033] Preferably, the first sintering temperature is 380-400°C, for example, 380°C, 382°C, 384°C, 386°C, 388°C, 390°C, 392°C, 394°C, 396°C, 398°C or 400°C.
[0034] Preferably, the first sintering time is 1-4 min, for example, it can be 1 min, 1.2 min, 1.5 min, 1.8 mins, 2 mins, 2.5 min, 3 min, 3.5 min or 4 min.
[0035] Preferably, in the second polytetrafluoroethylene emulsion containing inorganic filler, the mass percentage of polytetrafluoroethylene is 40-50%, for example, it can be 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49% or 50%.
[0036] Preferably, the second impregnation time is 3-15 s, for example, 3 s, 5 s, 6 s, 7 s, 8 s, 9 s, 10 s, 12 s or 15 s.
[0037] Preferably, the second drying temperature is 90-100°C, for example, it may be 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C or 100°C.
[0038] Preferably, the second drying time is 1-4 min, for example, 1 min, 1.2 min, 1.5 min, 1.8 mins, 2 mins, 2.5 min, 3 min, 3.5 min or 4 min.
[0039] Preferably, the temperature of the second heat treatment is 280-300°C, for example, it may be 280°C, 282°C, 284°C, 286°C, 288°C, 290°C, 292°C, 294°C, 296°C, 298°C or 300°C.
[0040] Preferably, the second heat treatment time is 1-4 min, for example, it can be 1 min, 1.2 min, 1.5 min, 1.8 mins, 2 mins, 2.5 min, 3 min, 3.5 min or 4 min.
[0041] Preferably, the second sintering temperature is 380-400°C, for example, 380°C, 382°C, 384°C, 386°C, 388°C, 390°C, 392°C, 394°C, 396°C, 398°C or 400°C.
[0042] Preferably, the second sintering time is 1-4 min, for example, it can be 1 min, 1.2 min, 1.5 min, 1.8 mins, 2 mins, 2.5 min, 3 min, 3.5 min or 4 min.
[0043] Preferably, the mass percentage of polytetrafluoroethylene in the first polytetrafluoroethylene emulsion is 40-50%, for example, it can be 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49% or 50%.
[0044] Preferably, the third impregnation time is 3-15 s, for example, it can be 3 s, 5 s, 6 s, 7 s, 8 s, 9 s, 10 s, 12 s or 15 s.
[0045] Preferably, the temperature of the third drying is 90-100°C, for example, it can be 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C or 100°C.
[0046] Preferably, the third drying time is 1-4 min, for example, it can be 1 min, 1.2 min, 1.5 min, 1.8 mins, 2 mins, 2.5 min, 3 min, 3.5 min or 4 min.
[0047] Preferably, the temperature of the third heat treatment is 280-300°C, for example, it may be 280°C, 282°C, 284°C, 286°C, 288°C, 290°C, 292°C, 294°C, 296°C, 298°C or 300°C.
[0048] Preferably, the third heat treatment lasts for 1-4 min, for example, 1 min, 1.2 min, 1.5 min, 1.8 mins, 2 mins, 2.5 min, 3 min, 3.5 min or 4 min.
[0049] Preferably, the temperature of the third sintering is 380-400°C, for example, it may be 380°C, 382°C, 384°C, 386°C, 388°C, 390°C, 392°C, 394°C, 396°C, 398°C or 400°C.
[0050] Preferably, the third sintering time is 1-4 min, for example, it can be 1 min, 1.2 min, 1.5 min, 1.8 mins, 2 mins, 2.5 min, 3 min, 3.5 min or 4 min.
[0051] Preferably, the mass percentage of polytetrafluoroethylene in the second polytetrafluoroethylene emulsion is 55-60%, for example, it can be 55%, 56%, 57%, 58%, 59% or 60%.
[0052] Preferably, the fourth impregnation time is 3-15 s, for example, it can be 3 s, 5 s, 6 s, 7 s, 8 s, 9 s, 10 s, 12 s or 15 s.
[0053] Preferably, the fourth drying temperature is 90-100°C, for example, it can be 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C or 100°C.
[0054] Preferably, the fourth drying time is 1-4 min, for example, it can be 1 min, 1.2 min, 1.5 min, 1.8 mins, 2 mins, 2.5 min, 3 min, 3.5 min or 4 min.
[0055] Preferably, the temperature of the fourth heat treatment is 280-300°C, for example, it may be 280°C, 282°C, 284°C, 286°C, 288°C, 290°C, 292°C, 294°C, 296°C, 298°C or 300°C.
[0056] Preferably, the fourth heat treatment lasts for 1-4 min, for example, 1 min, 1.2 min, 1.5 min, 1.8 mins, 2 mins, 2.5 min, 3 min, 3.5 min or 4 min.
[0057] Preferably, the fourth sintering temperature is 380-400°C, for example, 380°C, 382°C, 384°C, 386°C, 388°C, 390°C, 392°C, 394°C, 396°C, 398°C or 400°C.
[0058] Preferably, the fourth sintering time is 1-4 min, for example, it can be 1 min, 1.2 min, 1.5 min, 1.8 mins, 2 mins, 2.5 min, 3 min, 3.5 min or 4 min.
[0059] Compared with the prior art, the utility model has the following beneficial effects:
[0060] The demoulding cloth provided by the utility model is a non-porous and impermeable demoulding cloth, which is convenient to transfer and can be reused many times. It has no adhesive and only needs to be fixed with tape during laying. It is convenient to demould. At 100Pa, the area is 20cm 2 Under the conditions of, the air permeability of the release cloth provided by the utility model is as low as 0.01mm / s. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 It is a schematic diagram of the cross-sectional structure of the release cloth provided in Examples 1-3 of the present utility model;
[0062] Among them, 1 is the first polytetrafluoroethylene layer; 2 is the first polytetrafluoroethylene spacer layer; 3 is the glass fiber cloth; 4 is the second polytetrafluoroethylene spacer layer; 5 is the second polytetrafluoroethylene layer. DETAILED DESCRIPTION
[0063] The technical solution of the utility model is further described below in conjunction with the accompanying drawings and through specific implementation methods. Those skilled in the art should understand that the embodiments are only to help understand the utility model and should not be regarded as specific limitations of the utility model.
[0064] In the following embodiments, the surface density is tested according to GB / T4669; the thickness of each layer is tested by a thickness gauge (manufacturer: Mitutoyo, model: ID-C112XBS).
[0065] Example 1
[0066] A demoulding cloth, the schematic diagram of its cross-sectional structure is as follows Figure 1 As shown, it comprises a first polytetrafluoroethylene layer 1, a first polytetrafluoroethylene spacer layer 2, a glass fiber cloth 3, a second polytetrafluoroethylene spacer layer 4 and a second polytetrafluoroethylene layer 5 which are stacked in sequence; wherein the thickness of the first polytetrafluoroethylene layer is 0.011 mm; the thickness of the first polytetrafluoroethylene spacer layer is 0.008 mm; the thickness of the glass fiber cloth is 0.045 mm and the surface density is 49 g / m 2 ; The thickness of the second polytetrafluoroethylene spacer layer is 0.008mm; The thickness of the second polytetrafluoroethylene layer is 0.011mm; The total surface density of the first polytetrafluoroethylene layer and the second polytetrafluoroethylene layer is 58g / m 2 The total surface density of the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer is 74g / m 2 The first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer are respectively uniformly distributed with nano-silicon dioxide, and the mass percentage of nano-silicon dioxide in the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer is 20%; the thickness of the release cloth is 0.083 mm, and the surface density is 181 g / m 2 ;
[0067] The preparation method of the release cloth is as follows:
[0068] (1) After desizing the glass fiber cloth, the glass fiber cloth is immersed in a first polytetrafluoroethylene emulsion containing nano-silica for 9 seconds, wherein the mass percentage of polytetrafluoroethylene in the first polytetrafluoroethylene emulsion containing nano-silica is 35%, then glue is applied, dried at 94° C. for 90 seconds, then heat-treated at 285° C. for 90 seconds, and then sintered at 380° C. for 90 seconds; then immersed in a second polytetrafluoroethylene emulsion containing nano-silica for 9 seconds, wherein the mass percentage of polytetrafluoroethylene in the second polytetrafluoroethylene emulsion containing nano-silica is 45%, then glue is applied, dried at 94° C. for 90 seconds, then heat-treated at 285° C. for 90 seconds, and then sintered at 380° C. for 90 seconds, thereby forming a first polytetrafluoroethylene spacer layer and a second polytetrafluoroethylene spacer layer on both sides of the glass fiber cloth;
[0069] (2) The glass fiber cloth with the first polytetrafluoroethylene spacer and the second polytetrafluoroethylene spacer formed on both sides is immersed in a first polytetrafluoroethylene emulsion for 9 seconds, wherein the mass percentage of polytetrafluoroethylene in the first polytetrafluoroethylene emulsion is 50%, then glue is applied, dried at 94° C. for 90 seconds, then heat treated at 280° C. for 90 seconds, and then sintered at 380° C. for 90 seconds; then immersed in a second polytetrafluoroethylene emulsion for 9 seconds, wherein the mass percentage of polytetrafluoroethylene in the second polytetrafluoroethylene emulsion is 55%, then glue is applied, dried at 95° C. for 90 seconds, then heat treated at 285° C. for 90 seconds, and then sintered at 385° C. for 90 seconds, so as to form a first polytetrafluoroethylene layer on the first polytetrafluoroethylene spacer, and a second polytetrafluoroethylene layer on the second polytetrafluoroethylene spacer, and finally rolled to obtain the release cloth.
[0070] Example 2
[0071] A demoulding cloth, the schematic diagram of its cross-sectional structure is as follows Figure 1 As shown, it includes a first polytetrafluoroethylene layer 1, a first polytetrafluoroethylene spacer layer 2, a glass fiber cloth 3, a second polytetrafluoroethylene spacer layer 4 and a second polytetrafluoroethylene layer 5 which are stacked in sequence; wherein the thickness of the first polytetrafluoroethylene layer is 0.17 mm; the thickness of the first polytetrafluoroethylene spacer layer is 0.27 mm; the thickness of the glass fiber cloth is 0.55 mm and the surface density is 200 g / m 2 ; The thickness of the second polytetrafluoroethylene spacer layer is 0.27 mm; The thickness of the second polytetrafluoroethylene layer is 0.17 mm; The total surface density of the first polytetrafluoroethylene layer and the second polytetrafluoroethylene layer is 185 / m 2 The total surface density of the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer is 295g / m 2 The first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer are respectively uniformly distributed with nano-silicon dioxide, and the mass percentage of nano-silicon dioxide in the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer is 25%; the thickness of the release cloth is 1.43 mm, and the surface density is 680 g / m 2 .
[0072] Example 3
[0073] A demoulding cloth, the schematic diagram of its cross-sectional structure is as follows Figure 1 As shown, it comprises a first polytetrafluoroethylene layer 1, a first polytetrafluoroethylene spacer layer 2, a glass fiber cloth 3, a second polytetrafluoroethylene spacer layer 4 and a second polytetrafluoroethylene layer 5 which are stacked in sequence; wherein the thickness of the first polytetrafluoroethylene layer is 0.18 mm; the thickness of the first polytetrafluoroethylene spacer layer is 0.22 mm; the thickness of the glass fiber cloth is 0.34 mm and the surface density is 108 g / m 2; The thickness of the second polytetrafluoroethylene spacer layer is 0.22 mm; The thickness of the second polytetrafluoroethylene layer is 0.18 mm; The total surface density of the first polytetrafluoroethylene layer and the second polytetrafluoroethylene layer is 147 g / m 2 The total surface density of the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer is 195g / m 2 The first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer are respectively uniformly distributed with nano-silicon dioxide, and the mass percentage of nano-silicon dioxide in the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer is 25%; the thickness of the release cloth is 1.14 mm, and the surface density is 450 g / m 2 .
[0074] Example 4
[0075] A demoulding cloth, comprising a first polytetrafluoroethylene layer, a first polytetrafluoroethylene spacer layer, a glass fiber cloth, a second polytetrafluoroethylene spacer layer and a second polytetrafluoroethylene layer stacked in sequence; wherein the thickness of the first polytetrafluoroethylene layer is 0.004 mm; the thickness of the first polytetrafluoroethylene spacer layer is 0.008 mm; the thickness of the glass fiber cloth is 0.045 mm and the surface density is 49 g / m 2 ; The thickness of the second polytetrafluoroethylene spacer layer is 0.008mm; The thickness of the second polytetrafluoroethylene layer is 0.004mm; The total surface density of the first polytetrafluoroethylene layer and the second polytetrafluoroethylene layer is 12g / m 2 The total surface density of the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer is 74g / m 2 The first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer are respectively uniformly distributed with nano-silicon dioxide, and the mass percentage of nano-silicon dioxide in the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer is 20%; the thickness of the release cloth is 0.069 mm, and the surface density is 135 g / m 2 .
[0076] Example 5
[0077] A demoulding cloth, comprising a first polytetrafluoroethylene layer, a first polytetrafluoroethylene spacer layer, a glass fiber cloth, a second polytetrafluoroethylene spacer layer and a second polytetrafluoroethylene layer stacked in sequence; wherein the thickness of the first polytetrafluoroethylene layer is 0.011 mm; the thickness of the first polytetrafluoroethylene spacer layer is 0.006 mm; the thickness of the glass fiber cloth is 0.045 mm, and the surface density is 49 g / m 2 ; The thickness of the second polytetrafluoroethylene spacer layer is 0.006mm; The thickness of the second polytetrafluoroethylene layer is 0.011mm; The total surface density of the first polytetrafluoroethylene layer and the second polytetrafluoroethylene layer is 58g / m 2The total surface density of the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer is 28g / m 2 The first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer are respectively uniformly distributed with nano-silicon dioxide, and the mass percentage of nano-silicon dioxide in the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer is 20%; the thickness of the release cloth is 0.079 mm, and the surface density is 135 g / m 2 .
[0078] Example 6
[0079] A demoulding cloth, comprising a first polytetrafluoroethylene layer, a first polytetrafluoroethylene spacer layer, a glass fiber cloth, a second polytetrafluoroethylene spacer layer and a second polytetrafluoroethylene layer stacked in sequence; wherein the thickness of the first polytetrafluoroethylene layer is 0.23 mm; the thickness of the first polytetrafluoroethylene spacer layer is 0.27 mm; the thickness of the glass fiber cloth is 0.55 mm and the surface density is 200 g / m 2 ; The thickness of the second polytetrafluoroethylene spacer layer is 0.27 mm; The thickness of the second polytetrafluoroethylene layer is 0.23 mm; The total surface density of the first polytetrafluoroethylene layer and the second polytetrafluoroethylene layer is 265 / m 2 The total surface density of the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer is 295g / m 2 The first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer are respectively uniformly distributed with nano-silicon dioxide, and the mass percentage of nano-silicon dioxide in the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer is 25%; the thickness of the release cloth is 1.55 mm, and the surface density is 760 g / m 2 .
[0080] Performance Test:
[0081] (1) Air permeability test: The air permeability of the release cloth was tested using an air permeability tester (manufacturer: Sanjiang Instrument Co., Ltd., model: YG461E) in accordance with GB / T 5453 Determination of air permeability of textile fabrics; the test pressure was 100 Pa and the sample area was 20 cm 2 ;
[0082] (2) Glue permeability test: A release cloth is attached to the platform steel plate, and two layers of BMI resin prepreg (purchased from Guangdong Zhilian Aerospace Technology Co., Ltd., with a thickness of 0.2 mm) are laid on it, a layer of high-temperature isolation film (purchased from Shanghai Ligao Technology Co., Ltd., made of ETFE), and two layers of breathable felt (purchased from Shanghai Ligao Technology Co., Ltd., made of nylon staple fiber), and then a vacuum bag (purchased from Shanghai Ligao Technology Co., Ltd., made of PA6) is put into the autoclave, and the temperature is kept at 200°C and 0.6 MPa for 6 hours. After the mold is cooled, demold it, remove the vacuum bag, breathable felt, isolation film, BMI resin prepreg and release cloth, and observe whether the resin in the BMI resin prepreg penetrates into the mold surface.
[0083] Table 1
[0084] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Air permeability (mm / s) 0.01 0.01 0.01 10.36 3.36 0.01 Is there any glue seepage? none none none have have none
[0085] Analysis of the data results in Table 1 shows that the release cloth provided in Examples 1-3 can achieve the functions of being airtight and non-penetrating. By comparing Example 1 with Example 4, it can be found that when the first polytetrafluoroethylene layer and the second polytetrafluoroethylene layer are too thin, the release cloth is airtight and has glue penetration; by comparing Example 1 with Example 5, it can be found that when the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer are too thin, the release cloth is airtight and has glue penetration; by comparing Example 2 with Example 6, it can be found that when the thickness of the first polytetrafluoroethylene layer and the second polytetrafluoroethylene layer is too thick, the release cloth is airtight and has no glue penetration, but it will cause waste of materials.
[0086] The applicant declares that the utility model illustrates the detailed structural features of the utility model through the above-mentioned embodiments, but the utility model is not limited to the above-mentioned detailed structural features, that is, it does not mean that the utility model must rely on the above-mentioned detailed structural features to be implemented. Those skilled in the art should understand that any improvement to the utility model, equivalent replacement of the components selected by the utility model, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the utility model.
Claims
1. A release cloth, characterized in that: The demoulding cloth comprises a first polytetrafluoroethylene layer, a first polytetrafluoroethylene spacer layer, a glass fiber cloth, a second polytetrafluoroethylene spacer layer and a second polytetrafluoroethylene layer which are stacked in sequence; Inorganic fillers are evenly distributed in the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer.
2. The release cloth according to claim 1, characterized in that: The thickness of the release cloth is 0.07-1.5 mm.
3. The release cloth according to claim 1, characterized in that: The surface density of the release cloth is 120-700g / m 2 .
4. The release cloth according to claim 1, characterized in that: The thickness of the first polytetrafluoroethylene layer and the second polytetrafluoroethylene layer are independently 0.008-0.2 mm; The total surface density of the first polytetrafluoroethylene layer and the second polytetrafluoroethylene layer in the release cloth is 40-200 g / m 2 .
5. The release cloth according to claim 1, characterized in that: The thickness of the glass fiber cloth is 30-800 μm; The surface density of the glass fiber cloth is 40-200g / m 2 .
6. The release cloth according to claim 1, characterized in that: The thickness of the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer are independently 0.008-0.3 mm; The total surface density of the first polytetrafluoroethylene spacer layer and the second polytetrafluoroethylene spacer layer in the release cloth is 40-300 g / m 2 .
7. The release cloth according to claim 1, characterized in that: The inorganic filler includes any one of nano silicon dioxide, 3-aminopropyltriethoxysilane, nano magnesium titanate or triisostearoyl isopropyl titanate, or a combination of at least two thereof.
8. The release cloth according to claim 1, characterized in that: The mass percentage of the inorganic filler in the first polytetrafluoroethylene spacer layer is 10-25%.
9. The release cloth according to claim 1, characterized in that: The mass percentage of the inorganic filler in the second polytetrafluoroethylene spacer layer is 10-25%.
10. The release cloth according to claim 1, characterized in that: Under the condition of 100Pa, 20cm 2 The air permeability of the release cloth is not greater than 0.02 mm / s.
Citation Information
Patent Citations
Self-sticking type easily-washed polytetrafluoroethylene de-molded cloth for autoclave molding composite material and preparation method thereof
CN103741476A
Polytetrafluoroethylene glass fiber cloth demolding cloth
CN202246525U
Cited By
Composite material as well as preparation method, product and application thereof
CN121848777A